Flooded : requiem for Johnstown - Burg, Ann E. (Scholastic Press, 2020)
On May 31, 1889, the South Fork Dam built to create a man-made lake for America's wealthiest businessmen collapsed, unleashing twenty million tons of water onto the town of Johnstown, Pennsylvania, below; told in the voices of six children and many others this is the story of the ordinary people of the town, their losses and their survival--and of the bitter aftermath when those for whom the dam was built denied all responsibility for the shoddy dam and the unnatural disaster which it caused. Told in blank verse.